Initial coral assemblage drives benthic community response to different disturbance type events. - Ahmyia J Cacapit; Anela K Akiona; Esmeralda A Alcantar; Alex Araújo; Isa Bersamin; Ninoshka Betancourt; Daeyla' Boyd; Bostony Braoudakis; Zachary Capilitan; Angelica Dimas; Theresa Duncan; Clinton B Edwards; et al. (PLoS ONE)
An increase in the intensity and frequency of extreme environmental conditions due to anthropogenic climate change impacts coral reefs through myriad stressors, from elevated sea-surface temperatures to increased storm activity. A reef's response to these disturbances can be influenced by factors including taxonomic composition, life history strategies, or spatial patterning of the reef community members. We explored the disturbance-specific responses of coral reefs by following changes in benthic cover of major functional groups, community assemblage, and the response of common coral taxa at six islands across the central Pacific over the course of two years. We observed a decrease in average coral cover at four of the six islands, with differing underlying shifts in assemblage structure. Reefs with the highest pre-disturbance benthic coverage of Montipora spp. displayed significant increases in average hard coral cover compared to those where Acropora spp. was in the highest abundance; Acropora-dominated reefs showed significant declines in coral cover especially when exposed to the physical stress associated with a cyclone. Change in total coral cover was variable between islands within the same region, even among adjacent islands facing similar disturbance. These results highlight the importance of assemblage composition in influencing how benthic communities respond to major disturbance events such as thermal stress or cyclones. Improving our understanding of the drivers of differential community responses to disturbance will be important in predicting future changes in reef structure under changing ocean conditions.